Diagnostic accuracy of quadriceps strength-based criteria compared to handgrip-based criteria for diagnosing sarcopenia and severe sarcopenia in older adults - Prasert Assantachai (2022)
Aim:. Handgrip strength (HS) is an established parameter for sarcopenia diagnosis; however, a considerable proportion of older adults have some kind of hand abnormality or limitation that can prevent reliable hand muscle power testing. This study set forth to investigate the diagnostic accuracy of quadriceps strength (QS)-based criteria compared to handgrip strength (HS)-based criteria for diagnosing sarcopenia and severe sarcopenia in older adults. Setting and participants:. A total of 381 subjects aged ≥60 years who attended the outpatient geriatric clinic at Siriraj Hospital (Bangkok, Thailand) during 2015-2017 were recruited via convenience sampling. Patients who were ambulatory, able to communicate, and without metallic prosthesis or pacemaker were eligible for inclusion. Methods:. All consenting subjects underwent HS and QS testing, muscle mass measurement by bioelectrical impedance analysis, and gait speed analysis. The Asian Working Group for Sarcopenia (AWGS) 2019 consensus criteria were used as reference standard. Results:. The prevalence of sarcopenia and severe sarcopenia by HS-based criteria was 13.9% and 6.8%, respectively. In comparison, the prevalence of sarcopenia and severe sarcopenia by QS-based criteria was 14.7% and 10.2%, respectively. The sensitivity and specificity of QS-based criteria for diagnosing sarcopenia was 100% (95% confidence interval [CI]: 93.3-100%) and 99.1% (95%CI: 97.4-99.8%), respectively. The sensitivity and specificity of QS-based criteria for diagnosing severe sarcopenia was 88.5% (95%CI: 69.9-97.6%) and 95.5% (95%CI: 92.8-97.4%), respectively. Conclusions:. With very high sensitivity and specificity, QS-based diagnostic criteria could be used to diagnose sarcopenia and severe sarcopenia in older adults whose HS measurements could not be reliably obtained. Thai Clinical Trials Registry registration number:. TCTR 20200717004